2021
DOI: 10.3126/jsp.v2i01.43772
|View full text |Cite
|
Sign up to set email alerts
|

Glimpses on Emerging Alternative Living and Care Arrangements for Elderly People in Nepal

Abstract: This paper explores emerging alternative living and care arrangements for elderly people beyond the family, in Nepal. Family-based care and support for the old in Nepal are no longer guaranteed. Elderly people are abandoned or neglected mainly due to massive outmigration of the young and demographic change. As are sult, demand for place in old age homes and care centers is rapidly increasing. Exploratory visits at six different institutions, expert interviews and informal conversations with elderly residents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…[31][32][33] Caregiving for people with dementia is predominantly shouldered by family members, although home-based paid caregiving and formal caregiving in care homes are on the rise. 34 However, in the absence of formal training and low awareness among caregivers, including health care professionals in care homes, their care practices are largely based on personal experience, individual skills, and preferences, rather than on professional standards. 35,36 Concerning health services, a financial subsidy of Nepalese Rupee (NPR) 100,000 is provided for the treatment of dementia patients at selected hospitals.…”
Section: Dementia Context In Nepalmentioning
confidence: 99%
“…[31][32][33] Caregiving for people with dementia is predominantly shouldered by family members, although home-based paid caregiving and formal caregiving in care homes are on the rise. 34 However, in the absence of formal training and low awareness among caregivers, including health care professionals in care homes, their care practices are largely based on personal experience, individual skills, and preferences, rather than on professional standards. 35,36 Concerning health services, a financial subsidy of Nepalese Rupee (NPR) 100,000 is provided for the treatment of dementia patients at selected hospitals.…”
Section: Dementia Context In Nepalmentioning
confidence: 99%
“…Several studies have reported that extra income from remittances increases left-behind family members’ access to healthcare, education, nutrition, and other services in Nepal (Regmi, Paudel, and Williams 2014; Dhungana and Pandit 2014; Kim et al 2019; Bansak, Chezum, and Giri 2015; Nepal 2016). Tachibana et al (2019) found that increased international remittances reduced left-behind family members’ psychological distress after the 2015 earthquake in Nepal, but not mental disorders. Little research, however, has examined the consequences of such migration on non-financial dimensions for left-behind families, including the impact of adult children's migration on older parents’ mental health.…”
Section: Introductionmentioning
confidence: 95%
“…Building on a 2019 cross-sectional community-based survey conducted among older parents with adult children in Nepal, this article contributes toward understandings of migration's role in the psychological well-being of parents aged 60 years of above. With an increasing proportion of older people and an increasing trend of young adults leaving country for work and study affecting the traditional intergenerational support system among older people (Speck and Muller-Boker 2021), Nepal provides an important context, which may be similar to other LMICs (Gautam 2018).…”
Section: Introductionmentioning
confidence: 99%